In vitro clonal propagation of vulnerable ethnomedicinal cucurbit, red ball snake gourd (trichosanthes tricuspidata lour.) - RAJENDER. G; D. BHEEMANNA; P. SREENU; B. PRASAD; K. RAJENDER; T. CHRISTOPHER REUBEN (International Journal of Pharma and Bio Sciences, 2017)
Protocol for in vitro clonal propagation through shoot proliferation of nodal explants of a vulnerable ethnomedicinal Cucurbit, Trichosanthes tricuspidata Lour., was developed. Maximum number of shoots (20.16±0.79) and shoot length (4.16±0.79) was obtained on MS medium supplemented with BAP (4.0 mg/L) + TDZ (0.5 mg/L), after four weeks of culture. Microshoots cultured on MS medium supplemented with IBA (1.5 mg/L) produced adventitious roots. Cytological examination of root tips of plantlets (R1) obtained in this study did not reveal mitotic anomalies and the R1 plantlets were morphologically similar to mother plant. About 70% of R1 plantlets transferred to field condition survived and the vine grew well. These results demonstrated that in vitro clonal propagation of T. tricuspidata is technically viable.